Binary or Nonbinary Fission? Reproductive Mode of a Predatory Bacterium Depends on Prey Size - Karolina Pląskowska; Łukasz Makowski; Agnieszka Strzałka; Jolanta Zakrzewska-Czerwińska (mBio, 2023)
ABSTRACT Most bacteria, including model organisms such as Escherichia coli, Bacillus subtilis, and Caulobacter crescentus, reproduce by binary fission. However, some bacteria belonging to various lineages, including antibiotic-producing Streptomyces and predatory Bdellovibrio, proliferate by nonbinary fission, wherein three or more chromosome copies are synthesized and the resulting multinucleoid filamentous cell subdivides into progeny cells. Here, we demonstrate for the first time that the predatory bacterium Bdellovibrio bacteriovorus reproduces through both binary and nonbinary fission inside different prey bacteria. Switching between the two modes correlates with the prey size. In relatively small prey cells, B. bacteriovorus undergoes binary fission; the FtsZ ring assembles in the midcell, and the mother cell splits into two daughter cells. In larger prey cells, B. bacteriovorus switches to nonbinary fission and creates multiple asynchronously assembled FtsZ rings to produce three or more daughter cells. Completion of bacterial cell cycle critically depends on precise spatiotemporal coordination of chromosome replication with other cell cycle events, including cell division. We show that B. bacteriovorus always initiates chromosome replication at the invasive pole of the cell, but the spatiotemporal choreography of subsequent steps depends on the fission mode and/or the number of progeny cells. In nonbinary dividing filaments producing five or more progeny cells, the last round(s) of replication may also be initiated at the noninvasive pole. Altogether, we find that B. bacteriovorus reproduces through bimodal fission and that extracellular factors, such as the prey size, can shape replication choreography, providing new insights about bacterial life cycles. IMPORTANCE Most eukaryotic and bacterial cells divide by binary fission, where one mother cell produces two progeny cells, or, rarely, by nonbinary fission. All bacteria studied to date use only one of these two reproduction modes. We demonstrate for the first time that a predatory bacterium, Bdellovibrio bacteriovorus, exhibits bimodal fission and the mode of division depends on the size of the prey bacterium inside which B. bacteriovorus grows. This work provides key insights into the mode and dynamics of B. bacteriovorus proliferation in different pathogens that pose a major threat to human health due to their emerging antibiotic resistance (Proteus mirabilis, Salmonella enterica, and Shigella flexneri). The use of predatory bacteria such as B. bacteriovorus is currently regarded as a promising strategy to kill antibiotic-resistant pathogens. We find that B. bacteriovorus employs different chromosome replication choreographies and division modes when preying on those pathogens. Our findings may facilitate the design of efficient pathogen elimination strategies.